Improving the production technique of pat based on multicomponent fruit and berry paste - Zagorulko, Aleksey; Загорулько, Олексій; Kasabova, Kateryna; Касабова, Катерина; Zahorulko, Andrii; Загорулько, Андрій; Shydakova-Kameniuka, Olena; Шидакова-Каменюка, Олена; Ponomarenko, Nataliia; Пономаренко, Наталія Олександрівна; Bereza, Olena; Береза, Олена Юріівна; et al. (ЦЕНТР ПК ТЕХНОЛОГІЙ Український державний університет залізничного транспорту, 2024)
The object of this study is the technology of making fruit pat based on apple, apricot, and rosehip paste. To increase the organoleptic and physical-chemical quality indicators, the technology of functional fruit pat for functional purposes has been improved by using fruit and berry paste as a fruit base. Accordingly, a technique for the production of fruit and berry paste (apple 50 %, apricot 35 %, rosehip 15 %) was devised. The peculiarity of the technique is a short-term, 30–40 s, concentration at 52–54 °C in a rotary evaporator, which will positively contribute to the preservation of the functional ingredients of raw materials, unlike conventional batch vaporizers. The paste has an improved viscous structure and organoleptic properties compared to the control, which makes it possible to recommend it as a fruit base for pat. The viscosity of the pat mass based on the paste at 50 °C is 225 Pa∙s, which is 20 % higher than the control ("Fruit" pat), which will contribute to better structure formation. At the same time, the sample with the paste has better indicators of taste and smell, which can be characterized as natural and harmonious. The new pat has a natural orange saturated color and is characterized by a long-lasting consistency, and the content of functional ingredients significantly exceeds the control sample. The quantitative content of dietary fiber, vitamin A, C, β-carotene is important, according to which the devised pat based on the paste can be classified as a functional product. The new products are characterized by an organic composition of raw materials, do not contain artificial dyes and flavors, and the proposed technological solutions simplify the process of their production, which makes it possible to recommend the technology for implementation at craft enterprises Для підвищення органолептичних і фізико-хімічних показників якості удосконалено технологію функціонального фруктового пасту функціонального призначення з використанням фруктово-ягідної пасти як фруктової основи. Відповідно до цього була розроблена технологія виробництва плодово-ягідної пасти (яблуко 50 %, абрикос 35 %, шипшина 15 %). Особливістю методики є короткочасне, 30–40 с, концентрування при 52–54 °С у роторному випарнику, що позитивно сприятиме збереженню функціональних інгредієнтів сировини, на відміну від звичайних випарників періодичної дії. Паста має покращену в’язку структуру та органолептичні властивості порівняно з контролем, що дає змогу рекомендувати її як фруктову основу для пат. В’язкість пат-маси на основі пасти при 50 °С становить 225 Па∙с, що на 20 % вище за контроль (пат «Фруктовий»), що сприятиме кращому структуроутворенню. При цьому зразок з пастою має кращі показники смаку та запаху, які можна охарактеризувати як природні та гармонійні. Новий пат має натуральний помаранчевий насичений колір і характеризується тривалою консистенцією, а вміст функціональних інгредієнтів значно перевищує контрольний зразок. Важливе значення має кількісний вміст харчових волокон, вітаміну А, С, β-каротину, за якими розроблену пасту на основі пасти можна віднести до функціональних продуктів. Нова продукція характеризується органічним складом сировини, не містить штучних барвників та ароматизаторів, а запропоновані технологічні рішення спрощують процес її виробництва, що дає змогу рекомендувати технологію для впровадження на підприємствах ремісничого виробництва.
Удосконалення технології виробництва патів на основі багатокомпонентної плодово-ягідної пасти
Keywords: Turkish delight; плодово-ягідна сировина; удосконалення технології; technology improvement; multi-component fruit paste; багатоком-понентна плодово-ягідна паста